How the COVID-19 pandemic hit crime in Barcelona: Analysis of variation in crime trends - Díaz-Faes, Diego A. (European journal of criminology, 2023)
Objectives:To compare the observed and forecasted crime trends in Barcelona, using crime statistics from January 2018 to March 2021.Methods:We trained (seasonal) auto-regressive integrated moving average modelling (95% confidence intervals) using daily recorded crimes from January 2018 to February 2020. These models were then used to forecast crime data from March 2020 to March 2021 across four periods (lockdown, summer, fall and winter). Crime data were organized into two categories: property (burglary, theft) and violent crimes (robbery, assault, domestic violence and sexual offenses [rape, assault or abuse]).Results:Overall, crime levels for property and violent crimes during lockdown declined sharply from the forecasted levels. Theft, burglary, assault, robbery and sexual offenses exhibited general decreases throughout the study period, with the same sharp declines during the lockdown, progressive recovery in the summer, and steady or slight reductions from fall to March 2021. Only domestic violence differed, reaching the forecasted levels for all periods and surpassing the forecast for summer 2020.Conclusions:Our findings show how the pandemic has affected mid-term crime trends. They help to place the measures applied in the last year into context and to determine the most suitable policies to reduce crime during societal change.